A supramolecular material and its preparation method and application

By depositing 1,3,5-tris(4-aminophenyl)benzene and iron on the copper (111) crystal surface, supramolecular materials with N-Cu-N and N-Fe-N coordination bonds were solved The problem of the impact of N-Cu MOF size and morphology on properties has achieved efficient storage and separation of specific gas molecules, expanding the application of supramolecular materials.

CN119039609BActive Publication Date: 2025-01-10TIANJIN FIFTH CENT HOSPITAL (PEKING UNIV BINHAI HOSPITAL)
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411537781.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-01-10
Estimated Expiration
2044-10-31

AI Technical Summary

Technical Problem

The size and morphology of N-Cu MOF have a significant impact on its properties, but the existing technology is difficult to achieve fine controllable arrangement of different Cu-N coordination structures, which hinders the in-depth study of the Cu-N coordination structure formation mechanism and Application development.

Method used

By depositing 1,3,5-tris(4-aminophenyl)benzene and specific content of iron on the copper (111) crystal surface, the cis N-Cu-N coordination bond and the trans N-Fe are formed. -N coordination bonds use non-covalent weak bonds to form supramolecular materials with highly ordered structures, achieving efficient storage and separation of specific gas molecules.

Benefits of technology

This method not only changes the conformation of the composite, forms a tunable supramolecular material, realizes efficient storage and separation of specific gas molecules, and broadens the application range of supramolecular materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119039609B_ABST
    Figure CN119039609B_ABST
Patent Text Reader

Abstract

The invention belongs to the field of materials, and discloses a supramolecular material and a preparation method and application thereof. The supramolecular material is prepared by depositing a sub-monolayer of TAPB and iron on a copper (111) crystal surface, so that 1,3,5-tri(4-aminophenyl)benzene forms a cis-N-Cu-N coordination bond with copper and a trans-N-Fe-N coordination bond with iron. By introducing iron into the copper-amine complex, not only the conformation of the copper-amine complex can be changed, but also the obtained supramolecular material forms a supramolecular material with a highly ordered structure and controllability through non-covalent weak bond association (such as coordination bond, hydrogen bond, π-π stacking, etc.) between molecules, thereby realizing efficient storage and separation of specific gas molecules.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of materials and relates to a supramolecular material and a preparation method and application thereof. Background Art

[0002] Copper amine complexes usually exhibit square pyramidal coordination geometry in solution, forming a hybrid porous material known as metal-organic framework (MOF). MOFs can be synthesized using a variety of components and have a wide range of potential applications. Among the many developed MOFs, N-Cu MOFs have attracted particular attention due to their diverse structural configurations, enhanced stability through N-Cu interactions, good electrical conductivity, and excellent electrocatalytic ability. However, research on the characteristics and potential applications of N-Cu MOFs is still in its infancy. It is worth noting that the size and morphology of MOFs have a significant impact on their properties. However, MOF crystals usually exhibit different morphologies and sizes, which hinders in-depth studies on the formation mechanisms of different Cu-N coordination structures and the realization of controllable preparation strategies based on MOFs. Therefore, there are still challenges in the formation of different Cu-N coordination structures and the realization of fine controllable preparation in terms of MOF size.

[0003] Through the rational choice of components, surface-immobilized two-dimensional (2D) supramolecular coordination networks can mimic similar properties of three-dimensional (3D) MOFs in solution phase. Metal-organic interactions may involve unsaturated coordination, which is a significant advantage over the chemical reactions observed in 3D MOFs, due to the constraints of the 2D planar geometry of the substrate. This property enables the preparation of controllable supramolecular structures with tunable coordination numbers. In addition, the assembly process of 2D supramolecular networks and their complex configurations can be studied at the single-molecule level by scanning tunneling microscopy (STM). There have been several studies on N-Cu coordination structures on surfaces. Lin et al. synthesized 1D N-Cu-N supramolecular coordination chains using porphyrin compounds, revealing a dual N-Cu-N coordination structure that exhibits significant conformational flexibility. This flexibility allows deviations from linear arrangements on the surface. The exploration of the facet selectivity of N-Cu coordination structures on copper surfaces was ensured by single dehydrogenation and coordination reactions of 1,4-diaminonaphthalene on different coppers. Chi et al. constructed N-Cu-N coordination structures through a step-wise annealing process. Their study elucidated the potential of the amino group in 4,4''-diamino-p-phenylenediamine to coordinate with one or two copper atoms by breaking one or two hydrogen atoms. In addition, they described in detail the single and double dehydrogenation of the amino group in the TAPB molecule and the coordination with the Cu-increasing atom on copper (111). The comprehensive exploration of N-Cu coordination structures with variable coordination numbers in a controllable manner on the surface is expected to clarify the mechanism of controlling specific Cu-N coordination in 3D metal-organic frameworks.

[0004] In the present application, a novel supramolecular material is provided, which not only constructs the coordination structure of N-Cu-N, but also constructs the coordination structure of N-Fe-N, thereby broadening the application of supramolecular materials. Summary of the invention

[0005] The purpose of the present invention is to provide a novel supramolecular material. The supramolecular material is prepared by depositing a submolecular layer of 1,3,5-tri(4-aminophenyl)benzene and a specific content of iron on a copper (111) crystal surface, so that 1,3,5-tri(4-aminophenyl)benzene forms a cis N-Cu-N coordination bond with the copper (111) crystal surface and a trans N-Fe-N coordination bond with iron. In this way, not only the conformation of the original copper amine complex is adjusted, but also the obtained supramolecular material forms a supramolecular material with a highly ordered structure and controllability through non-covalent weak bond association (such as coordination bond, hydrogen bond, π-π stacking, etc.) between molecules, thereby realizing efficient storage and separation of specific gas molecules.

[0006] One of the purposes of the present invention is to provide a supramolecular material, wherein the supramolecular material is formed by coordination bonding of copper and iron with 1,3,5-tris(4-aminophenyl)benzene respectively;

[0007] When the coverage of 1,3,5-tri(4-aminophenyl)benzene on the copper (111) crystal plane surface is 0.4-0.8 monolayer, in the supramolecular material, 1,3,5-tri(4-aminophenyl)benzene and copper are connected by a cis N-Cu-N bond, and 1,3,5-tri(4-aminophenyl)benzene and iron are connected by a trans N-Fe-N bond.

[0008] Preferably, the mass ratio of 1,3,5-tris(4-aminophenyl)benzene to iron is (6-7):1.

[0009] Preferably, the supramolecular material has the following structure:

[0010] Formula (I).

[0011] A second object of the present invention is to provide a method for preparing a supramolecular material, the preparation method comprising the following steps:

[0012] At vacuum pressure of (0.5-1)×10 -10 Under 200-1000 K conditions, 1,3,5-tri(4-aminophenyl)benzene and iron were deposited on the surface of the copper (111) crystal plane and annealed at 380-400 K to obtain supramolecular materials.

[0013] Preferably, the copper is first subjected to sputtering treatment before deposition, and then subjected to annealing treatment, which is repeated 3-5 times;

[0014] Preferably, the sputtering process is an argon ion sputtering process, wherein the energy of the argon ions is 1-5 keV;

[0015] Preferably, the annealing temperature is 300-600°C and the annealing time is 10-20 minutes;

[0016] Preferably, the deposition method is thermal deposition;

[0017] Preferably, the 1,3,5-tris(4-aminophenyl)benzene and iron are thermally deposited on copper on different tantalum boats respectively;

[0018] Preferably, the rate of thermal deposition of 1,3,5-tri(4-aminophenyl)benzene is (4-5)×10 -11 g / s, time 200-400 s;

[0019] Preferably, the rate of the iron thermal deposition is (2-3)×10 -11 g / s, time 70-140 s;

[0020] Preferably, the annealing temperature is 380 K, and the annealing time is 30-50 minutes.

[0021] The third object of the present invention is to provide an application of the supramolecular material as described in the first object in gas separation.

[0022] Technical features and beneficial effects of the present invention:

[0023] In the present invention, the supramolecular material is prepared by depositing a submolecular layer of 1,3,5-tri(4-aminophenyl)benzene and a specific content of iron on a copper (111) crystal surface. The 1,3,5-tri(4-aminophenyl)benzene forms a cis N-Cu-N coordination bond with the copper (111) crystal surface and a trans N-Fe-N coordination bond with iron. This method can not only change the conformation of the complex, but also form a supramolecular material with a highly ordered structure and controllable properties through intermolecular non-covalent weak bond association (such as coordination bond, hydrogen bond, π-π stacking, etc.), thereby realizing efficient storage and separation of specific gas molecules. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is the process of TAPB molecules depositing onto the copper (111) crystal surface;

[0025] Figure 2 The composite structure obtained by depositing TAPB molecules onto the copper (111) crystal surface;

[0026] Figure 3It is the process of TAPB molecules and iron co-depositing onto the copper (111) crystal surface;

[0027] Figure 4 This is the process of TAPB molecules depositing on the silver (111) crystal surface;

[0028] Figure 5 The deposition process of TAPB molecules and TAPB molecules and iron on the copper (100) crystal surface;

[0029] Figure 6 This is the STM image of TAPB deposited as a monolayer on the copper (111) crystal surface;

[0030] Figure 7 This is the STM image of TAPB deposited as a monolayer on the copper (100) crystal surface;

[0031] Figure 8 is the adsorption geometry of TAPB-Cu complex on the copper (111) crystal surface;

[0032] Fig. 9 The adsorption geometry of TAPB-Cu complex on the copper (100) crystal plane. DETAILED DESCRIPTION

[0033] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0034] In order to enable those skilled in the art to more clearly understand the technical solution of the present application, the technical solution of the present application will be described in detail below in conjunction with specific examples. If the specific experimental conditions are not specified in the examples, they are usually in accordance with conventional conditions or the conditions recommended by the reagent company; the raw materials, reagents, consumables, etc. used in the following examples, unless otherwise specified, can be obtained through commercial channels.

[0035] The embodiment of the present application provides a supramolecular material, wherein the supramolecular material is formed by coordination bonding of copper and iron with 1,3,5-tris(4-aminophenyl)benzene respectively;

[0036] When the coverage of 1,3,5-tri(4-aminophenyl)benzene on the copper surface is 0.4-0.8 monolayer, in the supramolecular material, 1,3,5-tri(4-aminophenyl)benzene and the copper (111) crystal plane are connected by a cis N-Cu-N bond, and 1,3,5-tri(4-aminophenyl)benzene and iron are connected by a trans N-Fe-N bond.

[0037] It should be noted that during the formation of supramolecular materials, 1,3,5-tri(4-aminophenyl)benzene forms coordination structures with copper and iron respectively by removing two hydrogen atoms on the amino group; when forming the coordination structure, metal atoms, in-plane pressure, etc. play a key role in the two-dimensional coordination assembly.

[0038] When the material is composed only of copper and 1,3,5-tri(4-aminophenyl)benzene (TAPB) bonding, when the coverage of TAPB on the copper surface is a sub-monolayer (less than one molecular layer), the amino groups in TAPB undergo single dehydrogenation and connect to the copper atoms on the copper (111) crystal surface with trans N-Cu-N bonds; when the coverage of TAPB on the copper surface is at least a monolayer, the amino groups in TAPB undergo single dehydrogenation and connect to the copper atoms on the copper (111) crystal surface with cis N-Cu-N bonds.

[0039] To support the above conclusions, Figure 1 As shown in (a) in the figure, TAPB molecules are deposited and dispersed on the surface of the copper (111) crystal plane with a coverage of 0.8 monolayers. Figure 1 As shown in (b), after annealing at 350K for 1h, a two-dimensional network of hexagonal complexes (labeled as complexes 1, 2, and 3) was formed. The chirality of the coordination nodes in the hexagonal ring, clockwise and counterclockwise, divided these hexagonal complexes into three different types, and the probability of occurrence of these three types is very close. The molecular models of these complexes (complexes 1, 2, and 3) are shown in Figure 2 As shown in , all are trans conformations. In these compounds, each amino group of TAPB has lost a hydrogen atom. Further increasing the temperature did not produce significant changes.

[0040] To support the above conclusion, TAPB molecules were deposited and dispersed on the surface of copper (111) crystal plane with a full monolayer coverage, such as Figure 6 As shown in the figure, copper and TAPB molecules are assembled into triangular islands by van der Waals forces. This structure is caused by the plane compression pressure induced by high surface coverage after annealing at 300 K for 20 minutes. This structure disappears after further heating and loss of some free molecules. When the thermal annealing temperature is increased to 350 K, two different structures exist on the Cu substrate surface, such as Figure 1 As shown in (c) in the figure. Figure 1 In addition to the hexagonal complex in (b), a new close-packed hexagonal structure (labeled as complex 4) appears, located Figure 1 The upper right area of ​​(c) Figure 1 (d) is a high-resolution image of complex 4, and the molecular arrangement is as follows Figure 2 In this configuration, each TAPB molecule is connected to three other TAPB molecules in a cis coordination configuration through the copper atom. Figure 1 and Figure 2 It can be seen that the coordination configuration of complex 4 is cis, and the coordination configuration of complexes 1-3 is trans. The interaction between different coordination configurations leads to the irregular structure of the boundary area between the two networks, such as Figure 1 In this coordination process, each amino group of TAPB releases a single hydrogen atom, and further increasing the annealing temperature to 380 K does not cause any changes in the sample.

[0041] in, Figure 1 The imaging parameters of (a), (b), and (c) are: V = 5 mV, I = 0.1 nA; Figure 1 The imaging parameters in (d) are: V = 1 V, I = 1 nA; Figure 6 The imaging parameters are: V=1 V, I=0.02 nA.

[0042] In the present invention, when the coverage of TAPB on the copper surface is 0.4-0.8 monolayer (e.g., 0.4 monolayer, 0.5 monolayer, 0.6 monolayer, 0.7 monolayer, 0.8 monolayer), adding iron when copper and TAPB form a coordination structure can change the original connection conformation of TAPB and copper (111) crystal plane, so that the original trans conformation is changed to a cis conformation.

[0043] In some embodiments, the mass ratio of 1,3,5-tris(4-aminophenyl)benzene to iron is (6-7):1, for example, 6:1, 6.2:1, 6.4:1, 6.6:1, 6.8:1, 7:1, etc.

[0044] It should be noted that in the formed supramolecular complex, the quantitative ratio (also molar ratio) of deposited TAPB and iron is approximately 1:1, and the mass ratio of deposited TAPB and iron is approximately (6-7):1.

[0045] In some embodiments, the present application provides a method for preparing a supramolecular material, comprising: -10 Under the condition of 2400-1200 Å / min, 1,3,5-tri(4-aminophenyl)benzene and iron were deposited on the copper surface and annealed at a temperature of 380-400 K to obtain supramolecular materials.

[0046] In some embodiments, the copper is subjected to a sputtering treatment before being deposited, and then an annealing treatment, which is repeated 3-5 times.

[0047] In some embodiments, the sputtering process is an argon ion sputtering process, wherein the energy of the argon ions is 1-5 keV, for example, 1 keV, 1.5 keV, 2 keV, 2.5 keV, 3 keV, 3.5 keV, 4 keV, 4.5 keV, 5 keV, etc.

[0048] In some embodiments, the annealing treatment is performed at a temperature of 300-600° C. and for a time of 10-20 minutes.

[0049] Copper needs to be pretreated before use, preferably including sputtering and cleaning the copper with argon ion energy of 1-5 keV (preferably 5keV), and then annealing at 300-600℃ (preferably 500℃), repeating three rounds, each round lasting 10-20 minutes (preferably 15 minutes), and letting the sample cool naturally to room temperature after each round to ensure that the surface reaches the required cleanliness and crystal structure; and in the whole process, it is necessary to maintain a high vacuum environment, and closely monitor the sputtering current and sample temperature to avoid damage to the sample surface. It should be noted that in the text, when it comes to deposition on the substrate, the substrate needs to be pretreated in advance, and the pretreatment method adopts the preferred scheme.

[0050] In some embodiments, the deposition is performed by thermal deposition.

[0051] In some embodiments, the 1,3,5-tris(4-aminophenyl)benzene and iron are thermally deposited on copper (111) crystal plane on different tantalum boats.

[0052] In some embodiments, the rate of thermal deposition of 1,3,5-tris(4-aminophenyl)benzene is (4-5)×10 -11 g / s (e.g. 4×10 -11 g / s, 4.2×10 -11 g / s, 4.4×10 -11 g / s, 4.6×10 -11 g / s, 4.8×10 -11 g / s, 5×10 -11 g / s, etc.), and the time is 200-400 s (for example, 200 s, 220 s, 250 s, 280 s, 300 s, 320 s, 350 s, 380 s, 400 s, etc.).

[0053] The rate of iron deposition is (2-3)×10 -11 g / s (e.g. 2×10 -11 g / s, 2.2×10 -11 g / s, 2.4×10 -11 g / s, 2.6×10 -11 g / s, 2.8×10-11 g / s, 3×10 -11 g / s, etc.), and the time is 70-140 seconds (for example, 70 seconds, 80 seconds, 90 seconds, 100 seconds, 110 seconds, 120 seconds, 130 seconds, 140 seconds, etc.).

[0054] In some embodiments, the preparation method includes annealing the material obtained after deposition.

[0055] In some embodiments, the annealing temperature is 380 K, and the annealing time is 30-50 minutes, for example, 30 minutes, 32 minutes, 35 minutes, 38 minutes, 40 minutes, 42 minutes, 45 minutes, 48 ​​minutes, 50 minutes, etc.

[0056] In this application, TAPB and iron are deposited on the corresponding substrate by sublimation under ultra-high vacuum conditions. The deposition is carried out by STM experimental method using a Pt / Ir tip (90:10) and a scanning tunneling microscope (UNISOKU, USM-1500) at a pressure of 1.0×10 -10 The STM images were processed using WSxM.

[0057] Example 1

[0058] At a vacuum pressure of 1×10 -10 Torr conditions, TAPB and iron were deposited on the copper (111) crystal surface by thermal deposition, where the molar ratio of deposited TAPB and iron was 10:1, and the rate of TAPB thermal deposition was 4.5×10 -11 g / s, the deposition time is 300 s, and the rate of iron thermal deposition is 2.2×10 -11 g / s for 10 s; and then annealed at 380 K for 30 min, the coverage of TAPB deposited on the copper (111) crystal surface was 0.6 monolayers, constructing an irregular TAPB coordination structure, such as Figure 3 As shown in (a), in these structures, the coordination bond configuration is mainly trans, and there is also a small amount of cis coordination. The iron atoms are deposited continuously at a thermal deposition rate of 2.2×10 -11 g / s for 90 seconds, so that the molar ratio of deposited TAPB and iron is about 10:10, and a new arrangement appears, which is complex 5, and the arrangement includes cis coordination and trans coordination, such as Figure 3 As shown in (b) of Figure 3 (c) in the figure is further magnified and the corresponding molecular model of the structure is shown in Figure 3As shown in (d) in the figure. Given the low coverage of TAPB at this reaction temperature, the Cu-N-Cu interaction exists only in the trans-coordination form (e.g. Figure 1 As shown in Figure 5, it is speculated that the center of complex 5 is composed of complex 1 and is connected to each other through copper coordination. Each molecule in complex 1 interacts with another molecule through an N-Fe coordination bond. If it is cis-coordinated, then trans-coordination involves the participation of Cu atoms, while cis-coordination is promoted by Fe atoms. Figure 3 The scanning parameters for imaging in (a), (b), and (c) are: V=5 mV, I=0.1 nA.

[0059] To confirm the hypothesis of cis coordination between Fe and TAPB, similar experiments were performed on the Ag (111) plane. Figure 4 (a) shows the self-assembly of TAPB on the silver (111) crystal plane, with a coverage exceeding a monolayer, and loosely ordered parallel chains consisting of 4 molecular units are observed. Figure 4 (b) shows the molecular model of the chain structure, in which the middle pair of molecules is obviously slightly raised. Figure 4 After the iron is deposited and the sample is annealed at 380 K, a parallel chain consisting of four TAPB units is formed, as shown in (b). Figure 4 As shown in (c), the configuration of the complex is Figure 4 As shown in (d), in this structure, after one amino group in the middle TAPB molecule loses two hydrogen atoms, it coordinates with the two adjacent TAPB molecules. Similarly, after another amino group loses one hydrogen atom, it coordinates with the middle TAPB molecule. The middle TAPB molecule adopts a cis coordination configuration, while the peripheral molecules adopt a trans coordination configuration. This structure is then assembled into a long and thin chain under the action of weak van der Waals forces. After depositing iron and annealing at 380 K for 30 minutes, a unique two-dimensional network arrangement is formed, as shown in Figure 4 As shown in (e) in the figure. In this structure, each molecule removes two hydrogen atoms from its three amino groups and coordinates with two adjacent TAPB molecules to form N-Fe-N coordination bonds, all of which adopt a cis configuration. The molecular model of complex 7 is shown in Figure 4 As shown in (f) in . It should be noted that Figure 4 The chain configuration that appears in (c) disappears when the temperature is further increased, indicating the lack of chemical bonds between the chain structures and the low stability in the trans-coordinated structure. Figure 4 The imaging parameters of (a) and (e) are: V=0.1 mV, I=50 pA; the imaging parameters of (c) in Figure (4) are: V=5 mV, I=0.1 nA.

[0060] In some embodiments, when TAPB is deposited to monolayer coverage on a Cu(100) surface and then annealed at 350K, a parallel chain structure is formed, such as Figure 5 As shown in (a) in the figure, in this configuration, each molecule assumes the conformation of complex 8, in which one side of each TAPB unit is bonded to the adjacent TAPB through a cis coordination bond, and the other side forms a trans bond with another TAPB in the chain structure. Compared with the prevalence of trans coordination of TAPB observed on the copper (111) crystal surface, the ratio of cis to trans coordination on copper (100) is 2:1, and this difference can be attributed to the different periodicity and symmetry inherent in these surfaces. Comparison of the predicted coordination structures of TAPB on the copper (111) crystal surface and the copper (100) crystal surface shows a remarkable agreement with the experimental results (such as Figure 8 and Fig. 9 ).

[0061] For example, on the copper (111) crystal plane, the all-trans coordination arrangement (complex 1) results in a theoretical distance of 1.42 nm between Cu atoms, which is very close to the experimentally determined 1.50 nm. Similarly, in the chain configuration on copper (100) (complex 8), the actual distance between Cu atoms in cis coordination is 1.25 nm, which is very consistent with the theoretical model's 1.30 nm, while the distance in trans coordination is 2.80 nm, which is also consistent with the theoretical model's 2.90 nm. In complex 8, each amino group undergoes a single dehydrogenation reaction, maintaining consistent chirality within the same chain. Under submonolayer coverage, after annealing at 350K for 20 minutes, the following is formed. Figure 7 The ring structure shown, where (a) is an STM image of the assembled structure and (b) is a high-resolution image of the ring structure superimposed with the molecular model. In this eight-membered ring arrangement, the chirality of the TAPB molecules alternates, and only the molecule connected to the chain remains unchanged. Annealing the monolayer covered sample at 380K leads to interactions between the chain segments, such as Figure 5 As shown in (b) in . Figure 5 (d) in Figure 9 gives a possible molecular model of complex 9. In this interconnected node, the amino group undergoes a double dehydrogenation reaction compared with complex 8. However, after co-deposition of TAPB molecules and iron on the copper (100) surface and annealing at 380K, a ribbon-like structure was observed, as shown in Figure 9. Figure 5 In each strip, each molecule is cis-coordinated with two adjacent molecules. One amino group of each TAPB undergoes a didehydrogenation reaction, while the other two amino groups undergo a monodehydrogenation reaction, as shown in (c). Figure 5The composite 10 in (c) is shown in FIG. Among them, the imaging parameters of (a) and (c) in FIG. (5) are: V = 10 mV, I = 0.5 nA, and the imaging parameters of (b) are: V = 10 mA, I = 6 nA; the imaging parameters of (a) and (b) in FIG. (7) are: V = 10 mV, I = 0.5 nA.

[0062] Example 2

[0063] The vacuum pressure is 0.8×10 -10 Torr conditions, TAPB and iron were deposited on the copper (111) crystal surface by thermal deposition, where the molar ratio of deposited TAPB and iron was 10:1, and the rate of TAPB thermal deposition was 4×10 -11 g / s, the deposition time is 200 s, and the rate of iron thermal deposition is 2×10 -11 g / s for 6 seconds; then after annealing at 380 K for 20 minutes, the iron atoms were deposited again at a thermal deposition rate of 2×10 -11 The thermal deposition was performed at a rate of g / s for 60 seconds, so that the molar ratio of deposited TAPB and iron was about 10:10, wherein the coverage of TAPB deposited on the copper (111) crystal surface was 0.4 monolayers, and a composite was obtained.

[0064] It can be seen from the STM image that the structure of the composite obtained in Example 2 is consistent with that of the composite obtained in Example 1.

[0065] Example 3

[0066] At a vacuum pressure of 0.5×10 -10 Torr conditions, TAPB and iron were deposited on the surface of the copper (111) crystal surface by thermal deposition, where the molar ratio of TAPB to iron was 7:1, and the rate of TAPB thermal deposition was 5×10 -11 g / s, the deposition time is 400 s, and the rate of iron thermal deposition is 3×10 -11 g / s for 10 seconds; then, after annealing at 380 K for 30 minutes, the iron atoms were deposited again at a thermal deposition rate of 3×10 -11 The thermal deposition was carried out at a rate of g / s for 100 seconds, so that the molar ratio of deposited TAPB and iron was about 10:10, wherein the coverage of TAPB deposited on the copper (111) crystal surface was 0.8 monolayers, and a composite was obtained.

[0067] It can be seen from the STM image that the structure of the composite obtained in Example 3 is consistent with that of the composite obtained in Example 1.

[0068] The metal substrate of the composite obtained in Examples 1-3 was removed from the STM, and the sample was transferred to a gravimetric adsorption analyzer under the protection of an inert gas (such as argon). The carbon dioxide and nitrogen adsorption properties of the surface material were evaluated in the gravimetric adsorption analyzer. It was found that: the carbon dioxide adsorption amount of the composite in Example 1 was 1.6 mmol / g at 298 K and 1 bar, and the carbon dioxide / nitrogen adsorption ratio was 25; the carbon dioxide adsorption amount of the composite in Example 2 was 1.5 mmol / g at 298 K and 1 bar, and the carbon dioxide / nitrogen adsorption ratio was 24; the carbon dioxide adsorption amount of the composite in Example 3 was 1.2 mmol / g at 298 K and 1 bar, and the carbon dioxide / nitrogen adsorption ratio was 22.

[0069] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations on the present invention. A person skilled in the art may change, modify, replace and modify the above embodiments within the scope of the present invention without departing from the principles and intent of the present invention.

Claims

1. A supramolecular material, characterized in that: The supramolecular material is formed by the coordination bonding of copper and iron with 1,3,5-tris(4-aminophenyl)benzene respectively; The coverage rate of 1,3,5-tri(4-aminophenyl)benzene on the surface of copper (111) crystal plane is 0.4-0.8 monolayers. In the supramolecular material, 1,3,5-tri(4-aminophenyl)benzene and copper (111) crystal plane are connected by cis N-Cu-N bonds, and 1,3,5-tri(4-aminophenyl)benzene and iron are connected by trans N-Fe-N bonds. The mass ratio of 1,3,5-tris(4-aminophenyl)benzene to iron is (6-7):1; The supramolecular material has the following structure: Formula (I).

2. The method for preparing supramolecular materials according to claim 1, characterized in that: The preparation method comprises the following steps: At vacuum pressure of (0.5-1)×10 -10 Under the condition of 2000-2500 K, 1,3,5-tri(4-aminophenyl)benzene and iron were deposited on the surface of copper (111) crystal plane respectively, and annealed at 380-400 K to obtain supramolecular materials. Before the copper is deposited, it is firstly subjected to sputtering treatment and then subjected to annealing treatment, which is repeated 3-5 times; The sputtering process is an argon ion sputtering process, wherein the energy of the argon ions is 1-5 keV; The annealing temperature is 300-600° C., and the annealing time is 10-20 minutes.

3. The method for preparing supramolecular materials according to claim 2, characterized in that: The deposition method is thermal deposition; The 1,3,5-tri(4-aminophenyl)benzene and iron are thermally deposited on the copper (111) crystal plane on different tantalum boats.

4. The method for preparing supramolecular materials according to claim 3, characterized in that: The rate of thermal deposition of 1,3,5-tri(4-aminophenyl)benzene is (4-5)×10 -11 g / s, time is 200-400 s.

5. The method for preparing supramolecular materials according to claim 3, characterized in that: The rate of the iron thermal deposition is (2-3)×10 -11 g / s, time is 70-140 s.

6. The preparation method according to claim 2, characterized in that: The annealing temperature is 380 K, and the annealing time is 30-50 minutes.

7. Use of the supramolecular material according to claim 1 in separation of a mixed gas of carbon dioxide and nitrogen.

Citation Information

Patent Citations

  • Preparation method and gas separation application of copper-based microporous metal organic framework material

    CN110938213A

  • Cu (II) supramolecular complex and preparation method thereof

    CN111171057A